Driving force analysis of the consumption of copper resources in typical countries on LMDI method - Wang, Xiu; Liu, Guwang; Wang, Anjian; Liu, Chonghao; Liu, Qunyi (Frontiers in Earth Science, 2025)
Copper, a crucial strategic mineral, is extensively utilized across various sectorsglobally. However, the drivers of copper resource consumption (CRC) vary by country, influenced by their developmental stages, population sizes, and industrial levels. This study employs the Logarithmic Mean Divisia Index (LMDI) model to analyze the CRC of eight representative countries from 1997 to 2022, revealing distinct trends between developed and developing nations. The result shows, developed countries exhibited a decreasing CRC trend, attributable primarily to the intensity effect, whereas developing countries experienced an increase, predominantly driven by economic growth. Additionally, the structural effect in developed countries acted as a constraint on CRC growth, contrasting with its initial promotional role in developing countries before it became a restraining factor. This study is essential for crafting effective strategic policies for copper resources and ensuring their sustainable global development.